Comparison between some techniques of interpolators: An application in engineering - Devia Narváez, Diana Marcela (Scientia et Technica, 2019)
Abstract. This paper contains a detailed comparison between the Lagrange and Hermite polynomial interpolation when approximating a function. Initially the theoretical part about each interpolation procedure is exposed, followed by the exposure of the conditions of the comparative analysis between approximations, explaining the tests and calculating the error to be made